Experimental Evaluation of Test-Driven Development With Interns Working on a Real Industrial Project - Papis, Bartosz; Grochowski, Konrad; Subzda, Kamil; Sijko, Kamil (IEEE transactions on software engineering, 2022)
Context: There is still little evidence on differences between Test-Driven Development and Test-Last Development, especially for real-world projects, so their impact on code/test quality is an ongoing research trend. An empirical comparison is presented, with 19 participants working on an industrial project developed for an energy market software company, implementing real-world requirements for one of the company's customers. Objective: Examine the impact of TDD and TLD on quality of the code and the tests. The aim is to evaluate if there is a significant difference in external code quality and test quality between these techniques. Method: The experiment is based on a randomized within-subjects block design, with participants working for three months on the same requirements using different techniques, changed from week to week, within three different competence blocks: Intermediate, Novice and Mixed. The resulting code was verified for process conformance. The participants developed only business logic and were separated from infrastructural concerns. A separate group of code repositories was used to work without unit tests, to verify that the requirements were not too easy for the participants. Also, it was analysed if there is any difference between the code created by shared efforts of developers with different competences and the code created by participants isolated in the competence blocks. The resulting implementations had LOC order of magnitude of 10k. Results: Statistically significant advantage of TDD in terms of external code quality (1.8 fewer bugs) and test quality (5 percentage points higher) than TLD. Additionally, TDD narrows the gap in code coverage between developers from different competence blocks. At the same time, TDD proved to have a considerable entry barrier and was hard to follow strictly, especially by Novices. Still, no significant difference w.r.t. code coverage has been observed between the Intermediate and the Novice developers - as opposed to TLD, which was easier to follow. Lastly, isolating the Intermediate developers from the Novices had significant impact on the code quality. Conclusion: TDD is a recommended technique for software projects with a long horizon or when it is critical to minimize the number of bugs and achieve high code coverage.